Comparison of Static and Ambulatory Measurements of Illuminance and Spectral Composition That Can Be Used for Assessing Light Exposure in Real Working Environments. Issue 2 (3rd July 2019) - Adamsson, Mathias; Laike, Thorbjörn; Morita, Takeshi
ABSTRACT: Reliable measurements are of utmost importance when investigating the relationship between light and human reactions. The aim of the present study was to compare two methods for measuring light exposure in real working environments. Ambulatory recordings of illuminance and irradiance were compared with static field measurements of horizontal illuminance at the normal working position, average horizontal illuminance in the room, vertical illuminance at the position of the eye in the normal angle of gaze, and spectral composition of the light radiation at the normal working position and at the position of the eye in the normal angle of gaze. The ambulatory measurements were carried out during a 3-day experimental period and were repeated monthly throughout the year. The static field measurements in the subjects' offices were conducted five times during the year, in the morning and afternoon during one day. The relationship between the illuminances and irradiances measured with the portable instruments and the static measurements was statistically analyzed. Results from the analyses revealed that more than one third of the static measurements of vertical illuminances recorded were below 200 lx, and only 7% of the measurements exceeded 1000 lx. Measurements of the spectral composition of the light radiation in the rooms suggested that the light, although at a fairly low intensity, included relatively much radiation that can have a non-image forming effect. Furthermore, only a small number of significant correlations between the ambulatory and static measurements were found. Results from the t -tests showed that there were no differences between ambulatory measurements, and static measurements of horizontal illuminance at the normal position, average illuminance in the room and vertical illuminance at the position of the eye during three, five, and seven of the 10 measurements, respectively. There is a need to define appropriate parameters in order to describe the quality of a lit environment with respect to the non-image-forming effects of light radiation.